Síntese de compósito lignina/TiO2 com resíduo de Agave Sisalana e aplicação na remoção de bisfenol-A - Silva, Aleir Joice de Oliveira (2024)
Agave Sisalana (sisal) residue is an important source of lignin and its reuse reduces the environmental impact caused by inadequate disposal. Lignin is an aromatic copolymer found in the walls of plants that contains several functional groups in its structure, which contribute to its chemical reactivity and applications. Raw lignin has little efficiency in removing heavy metals and other organic contaminants, due to its interwoven and three-dimensional structure. Thus, lignin can be thermally and/or chemically modified to improve its biosorption capacity. One of the strategies that enables its application in the removal of emerging contaminants is the preparation of composites with metal oxides, including TiO2. In the present work, sisal residue was used as a source of lignin, and after extraction, the lignin was applied in the preparation of TiO2 composites to remove bisphenol-A through adsorption and photocatalytic degradation. Lignocellulosic characterization indicated that the sisal residue has a high lignin content. In the optimal condition of the experimental design for lignin extraction, lignin with 73% purity was obtained. The spectroscopic, textural, morphological and Zeta potential characterizations proved that the synthesized composites have high surface areas (>100 m2/g), homogeneous distribution of TiO2 particles and stable surface loads. The best results were obtained in the adsorption process, which resulted in a lignin/TiO2 composite with a maximum adsorption capacity of 13.7 mg L-1 capable of removing up to 97% of bisphenol-A. The adsorbent was used in six cycles, removing more than 70% in the third cycle, which indicates good stability.